(Waste Water Treatment of Tofu Industries by Chemical and Physical(Aeration ) Processes to the Decreasing of BOD5 and Suspended Solid) - Eko Susanto; Amelia Rachmatunisa (Warta Industri Hasil Pertanian, 1997)
The waste water of tofu industries cause enviromental poblem due to its high BOD and suspended solid values. The decomposition of organic matters in the waste water will result in cloudness of the water and awful smell. Therefore it is necessary to reduce their organic matters by coagulation process using chemicals and continued solid values. The result showed that the aeration, the lower the BOD and suspended values would be. The 22 hours aeration would decrease the BOD value up to 84.36% and suspended solids value op to 91.32%.